Fixational Eye Movements: Influence on the Accuracy in the Target Pointing Tasks - Laurutis, V.; Zemblys, R.; Buivis, L. (Elektronika ir Elektrotechnika, 2009)
In this research binocular fixational eye movement were studied. They reduce an accuracy of the defined target direction in the target pointing tasks, therefore possibilities of filtering them was analyzed. It was found that for both eyes two-dimensional scatter of the fixational eye movements in the horizontal direction is 1.5-2 times smaller than in the vertical. Two-dimensional scatter of the differences of the right and left eyes movements are significantly smaller than scatter of the each eye measured separately. Therefore, it was stated that fixational eye movements of the right and left eyes are correlated and using this phenomena gaze pointing accuracy could be increased. Scatter of the fixational eye movements is smaller when fixation is elicited to the visible spot in comparison to the imaginary target. Differences between means of the two-dimensional probability distribution of the fixational eye movements and the target directions stay within 10 min of arc. Standard deviations of the probability distributions changes only 10% when fixation spot is displaced up and down and changes 100% when it is displaced to the right and to the left. Ill. 3, bibl. 5 (in English; summaries in English, Russian and Lithuanian).